Innate lymphoid cells and the MHC - Robinette, Michelle L. (HLA, 2016)
Innate lymphoid cells (ILCs) are a new class of immune cells that include NK cells and appear to be the innate counterparts to CD4(+) helper T cells and CD8(+) cytotoxic T cells based on developmental and functional similarities. Like T cells, both NK cells and other ILCs also show connections to the MHC. In human and mouse, NK cells recognize and respond to classical and nonclassical MHC I molecules as well as structural homologues, whereas mouse ILCs have recently been shown to express MHC II. We describe the history of MHC I recognition by NK cells and discuss emerging roles for MHC II expression by ILC subsets, making comparisons between both mouse and human when possible.